The conceptual hydrogeological model of the Plitvice Lakes - Božidar Biondić (Geologia Croatica, 2010)
National Park Plitvice Lakes is located in the central part of the Dinaric karst region of Croatia. Plitvice Lakes are one of the most important and morphologically most attractive parts of the Croatia with the status of National Park since 1949 and with respected place in the list of World Natural Heritage by UNESCO since 1979. With its large karst springs, many lakes separated by tufa barriers and waterfalls, along with exceptional biodiversity represent a unique environment attractive for the arrival of many visitors and tourist development activities. This paper is aimed at defining a conceptual dynamic model of water resources in the Plitvice Lakes National Park. Lake is fed by groundwater from the mountain area of Mala Kapela and runoff from the lake system is directed towards the Black Sea basin. The whole area of the park is built of carbonate rocks of different degrees of natural permeability and very complex tectonic relations, which allowed springing of water, maintaining of the lakes and finally the loss of water in the karst underground downstream of Lower Lakes. Important hydrogeological function have poor permeable dolomites of Triassic age as a natural barrier to water from the mountainous area of Mala Kapela, through which the water flow, creating beautiful lakes and waterfalls. The largest lakes Prošćansko and Kozjak are generators of maintaining of high water quality of the whole system. Plitvice Lakes water after crossing the fault along the northeastern shore of Lake Kozjak starting to sink in the karst underground, which Kozjak Lake and Lower Lakes leads to a situation of high risk due to possible large-scale loss of water, if the natural functioning of the water system in relation to high water quality is disturbed.